THE STRATEGIC FRAMEWORK - State Planning Board, Government of Kerala (State Planning Board, 2015)
A prosperous, knowledge-driven and competitive economy, which optimises the use of resources and reduces environmental impact while ensuring high living standards for all is the vision. The mission to achieve sustainable prosperity rests on four pillars including economic, human, social and green. To attain quality growth benchmarking will be the central instrument for monitoring and improving the performance of the economy. Overall Kerala will be benchmarked against the Nordic countries. Education and health, the traditional strengths of Kerala will be the driving force of the new development strategy. Therefore, upgrading the quality of education and health to international standards, developing knowledge nodes within the state, promoting knowledge creation and diffusion are some key directions. The higher education system will create learning students and simultaneously create, disseminate and diffuse knowledge. Education and health will be inter-linked with all other sectors like agriculture, industry, tourism etc. Development of infrastructure is a crucial element and ICT is the lynchpin of a knowledge economy. Private investment and entrepreneurship will be encouraged. Social and environmental development will be mainstreamed. A systems approach to planning i.e. a coordinated effort of all the government departments, production systems, communities, NGOs and people will be adopted to implement this new development strategy. However, one has to strengthen institutions, improve governance and address factor market rigidities to create the enabling conditions for the new development strategy. A robust monitoring and evaluation system which promotes transparency and accountability and facilitates regular tracking of physical and financial performance of the plan will be created.